ENTOMOPATHOGENIC FUNGI A NEED OF HOUR IN MANAGEMENT OF BACTROCERA ZONATA; CHALLENGES AND OPPORTUNITIES - SHARIF, U; QAYYUM, MA; HAMEED, A; ANJUM, S; NAEEM-ULLAH, U; ISHTIAQ, M; TAHA, H (Biological and Clinical Sciences Research Journal, 2024)
The fruit flies (Diptera: Tephritidae) are polyphagous insect pests. Different methods are used to control this destructive pest including physical, chemical, genetic, and biological control. Biological control comprises predators, parasitoids, and pathogens. Now a day’s use of Entomopathogens is increasing very rapidly. Entomopathogenic fungi are one of the potential eco-friendly pest management alternatives to conventional pesticides. The most important Entomopathogenic fungi include Beauveria bassiana and Metarhizium anisopliae. These fungi have a specific set of characteristics including cuticle-degrading enzymes, toxins, and proteins which make them an excellent alternative to chemical control in insect pest management. Fungi generate a range of degrading enzymes to assist break down the insect cuticle and then emit poisonous secondary metabolites that aid the fungal invasion of the hemolymph. These degrading enzymes and other metabolites can be extracted and used as biopesticides against fruit flies. These biomolecules have great potential to be an alternative to synthetic chemical pesticides.